Lactose malabsorption based on breath hydrogen test in children with recurrent abdominal pain - Elizabeth Yohmi; Aswitha D Boediarso; Sri Rezeki S Hadinegoro (Paediatrica Indonesiana, 2004)
Background Recurrent abdominal pain (RAP) is common amongschool-age children. Previous studies found that lactose malab-sorption has an important role in RAP in children. Up to date, dataon the prevalence of lactose malabsorption in children with RAPin Indonesia has not been available.Objective To elicit the prevalence of RAP and lactose malabsorption inchildren with RAP, and to determine associated foods that cause RAPin children with and without lactose malabsorption, the frequency oflactose intolerance during breath hydrogen test (BHT), and also theonset and duration of the symptoms after a lactose load.Methods This was a cross-sectional study conducted on juniorhigh school students who suffered from recurrent abdominal pain.Results Of 1054 students screened, 157 (14.9%) fulfilled the Apley’scriteria for RAP. Of 157, 85 children were enrolled and underwentBHT. Fifty five of them (65%) were girls. Lactose malabsorptionwas found in 68 (80%) subjects. Milk and yogurt were the mostfrequent products that cause symptoms of RAP in our subjectswho mostly (80%) were malabsorber. Lactose intolerance duringBHT was found in 69 (81%) children. Symptoms appeared in 30minutes after lactose ingestion, and the most frequent symptomwas abdominal pain (44%). Lactose intolerance symptoms disap-peared in about 15 hours.Conclusions The prevalence of RAP in children aged 12-14 yearswas 14.9%. The prevalence of lactose malabsorption in childrenwith RAP was 80%. Milk and yogurt were the most frequent productsthat cause symptoms of RAP in our subjects who mostly weremalabsorbers. The frequency of lactose intolerance during BHTwas 81%, and the symptoms lasted within approximately 15 hours